Manipulating parameters of reinforcement to reduce problem behavior without extinction. Issue 2 (23rd February 2018) - Kunnavatana, S. Shanun; Bloom, Sarah E.; Samaha, Andrew L.; Slocum, Timothy A.; Clay, Casey J.
Abstract : Differential reinforcement of alternative behavior (DRA) most often includes extinction as a treatment component. However, extinction is not always feasible and it can be counter‐therapeutic if implemented without optimal treatment integrity. Researchers have successfully implemented DRA without extinction by manipulating various parameters of reinforcement such that alternative behavior is favored. We extended previous research by assessing three participants' sensitivities to quality, magnitude, and immediacy using arbitrary responses and reinforcers that maintain problem behavior. The results were used to implement an intervention for problem behavior using DRA without extinction. Our findings indicate that arbitrary responses can be used to identify individual and relative sensitivity to parameters of reinforcement for reinforcers that maintain problem behavior. Treatment was effective for all participants when we manipulated parameters of reinforcement to which they were most sensitive, and, for two participants, the treatment was less effective when we manipulated parameters to which they were least sensitive.